2003
DOI: 10.1016/s1097-2765(03)00058-3
|View full text |Cite|
|
Sign up to set email alerts
|

PP2C Phosphatases Ptc2 and Ptc3 Are Required for DNA Checkpoint Inactivation after a Double-Strand Break

Abstract: Saccharomyces cells suffering a DNA double-strand break (DSB) ultimately escape checkpoint-mediated G2/M arrest either by recovery once the lesion is repaired or by adaptation if the lesion proves irreparable. Cells lacking the PP2C-like phosphatases Ptc2 and Ptc3 are unable to adapt to a HO-induced DSB and are also defective in recovering from a repairable DSB. In contrast, overexpression of PTC2 rescues adaptation-defective yku80Delta and cdc5-ad mutants. These effects are not explained by alterations either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 37 publications
12
146
0
Order By: Relevance
“…It has been reported that Ptc2 and Ptc3, two members of the PP2C family, bind to Rad53 and inactivate Rad53-dependent pathways in S. cerevisiae. 21 Considering our results, it is likely that Ptc2 and Ptc3 inactivate Rad53 by dephosphorylating it. Furthermore, we provide evidence suggesting that Wip1 may (Figures 4 and 5).…”
Section: Antagonistic Effect Of Wip1 On Chk2-dependent Apoptosismentioning
confidence: 62%
See 1 more Smart Citation
“…It has been reported that Ptc2 and Ptc3, two members of the PP2C family, bind to Rad53 and inactivate Rad53-dependent pathways in S. cerevisiae. 21 Considering our results, it is likely that Ptc2 and Ptc3 inactivate Rad53 by dephosphorylating it. Furthermore, we provide evidence suggesting that Wip1 may (Figures 4 and 5).…”
Section: Antagonistic Effect Of Wip1 On Chk2-dependent Apoptosismentioning
confidence: 62%
“…20 On the other hand, in Saccharomyces cerevisiae, the type 2C protein phosphatases (PP2C), Ptc2 and Ptc3, bind to Rad53, the S. cerevisiae orthologue of Chk2, and inactivate Rad53 presumably by dephosphorylating Rad53, leading to checkpoint inactivation upon a DNA double-strand break. 21 Thus, it can be assumed that protein phosphatases may mediate the termination of DNA damage-induced cell-cycle checkpoint arrest to restart cell cycle by dephosphorylating and inactivating checkpoint kinases. Despite the high degree of conservation between cell-cycle checkpoint in yeast and mammals, it remains unknown whether or not protein phosphatases are involved in the termination of DNA damage-induced cell-cycle checkpoint arrest in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that the Ptc2 and Ptc3 phosphatases in budding yeast interact with and downregulate the Rad53 checkpoint kinase after a DNA DSB (Leroy et al, 2003). Ptc2 and Ptc3 belong to the PP2C family of protein phosphatases.…”
Section: Wip1 Selectively Reverses the Action Of Atm On Chk2mentioning
confidence: 99%
“…Rad53 is the budding yeast ortholog of Chk2. Previously, we showed that two type 2C protein phosphatases (PP2C), Ptc2 and Ptc3, were required for inactivation of the Rad53 DNA damage checkpoint during adaptation and recovery from a DNA DSB in Saccharomyces cerevisiae (Leroy et al, 2003). In this study, we sought to test the conservation of this pathway by looking for an orthologous human PP2C phosphatase able to inactivate Chk2.…”
Section: Introductionmentioning
confidence: 99%
“…Although the process of recovery is conserved in budding yeast, the sole member of the PLK family in this organism, Cdc5, and some of the homologs of the Plk1 substrates mentioned above are not involved in the recovery process in this organism (Jin and Wang 2006;Vaze et al 2002). Additional mechanisms may be in place in lower eukaryotes to promote recovery after DNA repair is completed (Guillemain et al 2007;Leroy et al 2003;O'Neill et al 2007). …”
Section: Cellular Recovery From Dna Damagementioning
confidence: 99%